2022
DOI: 10.18231/j.ijpo.2022.055
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological study of cervical Pap smear based on the Bethesda system 2014

Abstract: : The Papanicolaou (Pap) smear used worldwide for cervical screening was developed by Dr George Papanicolaou in 1940s. The Pap smear is a simple, safe and effective test to detect cervical cancer at an early stage.: To study the spectrum of lesions in cervical Pap smear based on The Bethesda System(TBS) 2014 and to determine frequency of premalignant and malignant lesions.: The present prospective study included 200 cases above 20 years of age. The cytological interpretation of smears were made according to TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…12 In the study conducted by Sinchana et al, 18 cases (9%) were reported as ECA, which were in line with this study, where 53 cases (9%) were also reported as ECA. 11 In a study conducted by Sharma et al, in 2021, the total number of ASCUS cases was 15 (3.3%), which was in line with this study where 21 cases (3.74%) were reported as such. 14 The same study reported five cases (1.2%) as LSIL, whereas in our study, two cases (0.32%) were reported as LSIL.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…12 In the study conducted by Sinchana et al, 18 cases (9%) were reported as ECA, which were in line with this study, where 53 cases (9%) were also reported as ECA. 11 In a study conducted by Sharma et al, in 2021, the total number of ASCUS cases was 15 (3.3%), which was in line with this study where 21 cases (3.74%) were reported as such. 14 The same study reported five cases (1.2%) as LSIL, whereas in our study, two cases (0.32%) were reported as LSIL.…”
Section: Discussionsupporting
confidence: 88%
“…In a study conducted by Sinchana et al, two cases (1%) were reported as AGCs (NOS), which was in line with this study where seven cases (0.97%) were also reported as AGCs (NOS). 11 In this study, one case was reported as poorly differentiated malignancy on pap smear, whereas no such cases were reported in the comparative studies. 11,12,14 Histopathological examination was advised for all ECA category cases and for those cases that were clinically suspicious though unsatisfactory on cytology.…”
Section: Limitations Of the Studymentioning
confidence: 61%
See 3 more Smart Citations